2013
DOI: 10.1002/eji.201343713
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation in lung immunity — The protective and pathologic Th17 response in infection

Abstract: Th17 cytokines can play both protective and pathologic roles in the airway. An emerging theme in Th17 cytokine biology is that these responses can mediate tissue pathology when downstream effector cells are dysfunctional such as neutrophils lacking functional NADPH oxidase in the case of chronic granulomatous disease or epithelial cells lacking appropriate ion transport, as in the case of cystic fibrosis. In this mini-review we highlight recent advances in the protective and pathologic roles of Th17 cytokines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 67 publications
2
21
0
4
Order By: Relevance
“…Airborne insults such like cigarette smoke, diesel dusts, bacterial infection and allergens induce the release of chemokines IL6, IL8, TNF, IL-1, GM-SCF, MCP-1 from airway epithelial cells [12, 20, 21, 29, 47, 58, 59, 68, 77, 98, 101, 115, 117, 119, 120, 143]. Release of these cytokines either recruit neutrophils directly [140] or induce IL-17 release from T H 17 cells [137]. The outcome of neutrophil enrichment is a cytokine profile, which is dominated by TNF-α, IL-1β, IL-6, IL-17, IL-18, IL-32 and TGF-β [14] (Fig.…”
Section: Tjs In Early Lung Inflammation Copd and Acute Lung Injurymentioning
confidence: 99%
“…Airborne insults such like cigarette smoke, diesel dusts, bacterial infection and allergens induce the release of chemokines IL6, IL8, TNF, IL-1, GM-SCF, MCP-1 from airway epithelial cells [12, 20, 21, 29, 47, 58, 59, 68, 77, 98, 101, 115, 117, 119, 120, 143]. Release of these cytokines either recruit neutrophils directly [140] or induce IL-17 release from T H 17 cells [137]. The outcome of neutrophil enrichment is a cytokine profile, which is dominated by TNF-α, IL-1β, IL-6, IL-17, IL-18, IL-32 and TGF-β [14] (Fig.…”
Section: Tjs In Early Lung Inflammation Copd and Acute Lung Injurymentioning
confidence: 99%
“…Acidification of the airways in CF patients decreases antimicrobial protein function , providing an explanation for increased colonization by opportunistic pathogens. High bacteria burdens coupled with impaired antimicrobial activity may contribute to the pathological effects associated with IL‐17 in CF (reviewed in ).…”
Section: Pulmonary Epithelial Immune Barriersmentioning
confidence: 99%
“…These two members share the highest degree of homology and show similar functions. Numerous studies have demonstrated that IL-17 and IL-17F are critical molecules in mucosal host defense and inflammatory diseases (Chen and Kolls, 2013; Kumar and Subramaniyam, 2015; Way et al, 2013). Infections and inflammatory diseases increase the accumulation of IL-17-producing cells in lung tissue.…”
Section: Introductionmentioning
confidence: 99%